2020
DOI: 10.1016/j.nec.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Automation Advances in Stereoelectroencephalography Planning

Abstract: The past decade has seen a significant shift in the number of centers performing intracranial electroencephalography from subdural grids and strips to stereoelectroencephalography (SEEG). Unlike grid and strip insertion or other stereotactic procedures in which the cortical surface is visualized, SEEG involves insertion of an electrode through a bolt anchored into the skull. Due to the multidisciplinary nature of SEEG trajectory planning, it often is time-consuming and iterative. Computer-assisted planning imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In generating these priors, we purposefully excluded trajectories that targeted unique patient-specific abnormalities, such as focal cortical dysplasia, as these would not be generalizable when considering trajectory planning in other patients. In such cases, computer-assisted planning can still be utilized using the segmentation of the lesion as the target and allow the algorithm to choose the most appropriate entry point (12). As a further analysis, we implemented a K-NN classifier as part of an adaptive learning algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In generating these priors, we purposefully excluded trajectories that targeted unique patient-specific abnormalities, such as focal cortical dysplasia, as these would not be generalizable when considering trajectory planning in other patients. In such cases, computer-assisted planning can still be utilized using the segmentation of the lesion as the target and allow the algorithm to choose the most appropriate entry point (12). As a further analysis, we implemented a K-NN classifier as part of an adaptive learning algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The EpiNav™ algorithm generates SEEG trajectories based on optimization of user-defined parameters, which include intracerebral length, drilling angle to the skull, gray matter sampling ratio, minimum distance from vasculature, risk score, and avoidance of critical structures ( 12 ). For an in-depth discussion on planning parameter selection see ( 13 ). The user-defined parameters applied during this study are shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations